ANALYSIS OF FINANCIAL STATEMENTS TO MEASURE THE EFFECTIVENESS OF THE COMPANY'S FINANCIAL PERFORMANCE IN PT. RETABTAMA - Yeni Lasmayanti Martika; Ruhenda (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This research was conducted with the aim of ensuring the company's financial flow and the extent to which the company's effectiveness and efficiency in using its resources, as well as the good and bad financial conditions at PT. Retabtama. The research method carried out in this study uses a quantitative research approach the data collection technique used is the documentation method, in which the researcher obtains data on the company's financial statements and other information related to the company. And the data analysis technique used in measuring the company's financial performance is to use of an analytical tool in the form of financial ratios. In measuring the company's financial performance here, the researcher uses financial ratios in the form of Solvency Ratios represented by the Debt Assets Ratio, Debt Equity Ratio, and Long Term Debt to Equity Ratio, besides that they also use Profitability Ratios which are represented by Gross Profit Margin, Net Profit Margin, Return on Investment and Return on Equity. The result of this research is that PT. Retabtama when viewed from the Solvency Ratio shows that the company is in a very good condition where the company is able to manage its debt. Besides that, it is also seen from the Profitability Ratio that the company is less effective in utilizing assets and managing capital so the company has decreased in terms of income and profit.